ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN TERHADAP KEPUASAN PEMBELIAN PADA PT. ASKOTAMA INTI NUSANTARA - Bambang Ermansyah Saragih (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
The  development  of  the  business  world  in  Indonesia  iscurrently  growing  rapidly,  considering  that  it  has entered  the  era  of  globalization  so  that  the  business  world  isrequired to develop rapidly. Consumers prioritize product quality, affordable prices and the company's advertisementsare not excessive. Creating purchase satisfaction is a challenge for entrepreneurs because a buyer is now increasinglycritical in choosing the type of product and must match his expectations. The purpose of this study is to determine:Analysis  of  the  Effect  of  Product  Quality, Price  and  Advertising  on  Purchase  Satisfaction  at  PT.  Askotama  IntiNusantara.“The sampling technique used in this study the author uses the Random Sampling technique (Randomlyon All  Consumers) where  each member of the  population has the  same opportunity  to be  selected as  the overallsample, but the sample in this study is the  entire population that is sampled .“The results obtained that partially andsimultaneously there is a positive and significant influence between Product Quality, Price, Advertising on Purchase Satisfaction.